Variantes angio-tomodensitométriques de l’aorte abdominale chez le sujet adulte au Togo - FOSSO Calliclès Stell; N’TIMON Bidamin; SOUHO Bénédicte; GBANDE Pihou; DAGBE Massaga; LAWSON-ANANISSOH Laté Mawuli; SONHAYE Lantam; AGODA-KOUSSEMA Lama Augustin Kegdigoma, (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2025)
Objective: To describe the morphology and biometrics of the abdominal aorta using computed tomography in adult togolese individuals. Materials and Methods: This descriptive cross-sectional survey was conducted with prospective data collection between May 5th and July 4th, 2024, across computed tomography units in two hospitals located in Lomé and one in Kara, Togo. Data of patients who underwent contrast-enhanced abdominopelvic CT scans with an arterial phase were retrieved from the PACS (Picture Archiving and Communication System). For each participant, the level of the aortic hiatus, site of bifurcation of the aorta into the iliac arteries, type of aortic trajectory, and diameters of the aorta above and below the renal arteries were documented. Results: Among the 124 patients included in the analysis, 71 (57.3%) were female, yielding a male-to-female ratio of 0.74. The average age of the participants was 51.7 ± 16.3 years, and the median age was 55.5 years (interquartile range = 25). The aortic diaphragmatic hiatus was identified at the level of the twelfth thoracic vertebra (T12) in 55.6% of subjects. The aortoiliac bifurcation was situated at the level of the fourth lumbar vertebra in 78.2% of participants. A linear course of the aorta was observed in 66.1% of cases, whereas a non-linear trajectory was noted in 33.9%. The incidence of non-linear aortic trajectory was five-fold higher among individuals aged over 56 years than among those aged 56 years or younger (p = 0.001). The mean diameter of the abdominal aorta was 20.9 ± 3 mm above the renal arteries and 15.8 ± 2.2 mm below them. The diameters of the aorta above and below the renal arteries were found to be significantly larger in males than in females, as well as in individuals over the age of 56 compared to those aged 56 or younger (p < 0.001). No significant differences were observed regarding sex in relation to the aortic trajectory, height of the aortic hiatus, or level of aortic bifurcation. Conclusion: The non-linear trajectory of the abdominal aorta is more frequent in individuals over 56 years old, and its caliber is significantly greater in men compared to women. Résumé Objectif : Décrire à la tomodensitométrie la morphologie et la biométrie de l’aorte abdominale chez le sujet adulte togolais. Matériels et méthodes : Étude transversale descriptive avec collecte prospective de données entre le 05 mai et le 04 juillet 2024 au sein de l'unité de scanner de trois établissements hospitaliers dont deux à Lomé et un à Kara, Togo. Les données des patients ayant réalisé un examen tomodensitométrique de la région abdomino-pelvienne avec injection de produit de contraste au temps artériel ont été recueillies sur le PACS. La hauteur du hiatus aortique, de la bifurcation aorto-iliaque, le type de trajet et le calibre de l’aorte abdominale sus et sous rénale ont été déterminés chez chaque participant. Résultats : Parmi les 124 patients inclus dans l’étude, 71 (57,3%) étaient des femmes (sex-ratio=0,74). L’âge moyen des participants était de 51,7 ± 16,3 ans et l’âge médian de 55,5 (intervalle interquartile=25) ans. Le hiatus diaphragmatique de l’aorte était localisé à hauteur de la douzième vertèbre thoracique chez 55,6% des participants. La bifurcation aorto-iliaque était située à hauteur de la quatrième vertèbre lombaire chez 78,2% des participants. Le trajet de l’aorte était rectiligne chez 66,1% des participants et ne l’était pas dans 33,9% des cas. Le trajet non rectiligne de l’aorte était cinq fois plus fréquent chez les sujets de plus de 56 ans par rapport à ceux âgés de moins de 56 ans (p=0,001). Le calibre moyen de l’aorte abdominale sus-rénale était de 20,9 ± 3 mm et celui de l’aorte sous-rénale était de 15,8 ± 2,2 mm. Le calibre de l'aorte sus et sous-rénale était significativement plus important chez les hommes (p < 0,001). De même, le calibre de l’aorte des sujets de plus de 56 ans était plus important comparativement à ceux âgés de 56 ans ou moins (p < 0,001). Le sexe n’avait pas d’influence sur le trajet de l’aorte, la hauteur du hiatus diaphragmatique et la bifurcation aorto-iliaque. Conclusion :Le trajet non rectiligne de l’aorte abdominale est plus fréquent chez les personnes âgées de plus de 56 ans et son calibre est plus important chez les hommes comparativement aux femmes.